A study on the relationship between quality work life and productivity among staff in UiTM Jengka, Pahang / Nor Aliza Ismail, Nurul Idayu Sapri and Noraniza Idris - Ismail, Nor Aliza; Sapri, Nurul Idayu; Idris, Noraniza (2010)
The purpose of this research is to help organization to identify the steps or actions that can be taken in order to retain people who are most important resources in the organization. The findings will give information to the company that are useful to assist decision maker in identifying the important elements in order to develop strategies to improve the quality of working condition in each organization. Elements of Quality Work Life can be divided into four elements. They are adequate and fair compensation, work and total life space, opportunity for continued growth and security and safe and healthy work condition. Queationnaire was prepared and a research had been conducted in Universiti Teknologi Mara, Jengka branch. The result shows that most of the respondents agreed that the two elements which are work and total life space and opportunity for growth can increase their performance and productivity. As a conclusion, work and total life space and opportunity for growth can give positive effects to the workers and organization through their good performance and productivity. This study also provided recommendations that can be used by the workers and organizations.